BIOSISTEMATIKA DUKU, KOKOSAN DAN LANGSAT DI INDONESIA - , Laila Hanum, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Lansium domesticum Corr. is popular fruits plant occurs mainly in South-East Asia especially in Java-Indonesia, Malay Peninsula, and the Philippines and where it is widely distributed and grown. The plant is classified under the family Meliaceae. There are three different types of L. domesticum which are commonly grown in Indonesia, namely duku, kokosan and langsat. The morphological appearance of all cultivar is nearly the same, and identification of the cultivar is very difficult for growers. The aims of this study were to collect, characterize and identify variability of duku, kokosan and langsat fruit in Indonesia, to determinate taxonomycal status of phylogenetic relationship within different cultivar of L. domesticum. Exploration has been done using purposive sampling methods by visiting some horticulture centers in Indonesia including Sumatera, Jawa, Kalimantan and Kepulauan Maluku. Morphological approach included herbarium, morphological characterization, description, identification, and relatedness analysis. Analysis of phenetic relatedness among duku, kokosan and langsat from Indonesia were investigated using random amplified polymorphic DNA (RAPD) markers. Eleven primers (OPA-01, OPA-02, OPA-10, OPB-07, OPB-11, OPB-12, OPB-15, OPT-16, OPU-14, OPU-19, and OPU-20) were used for amplification. Phylogenetic relationship within different cultivar of L. domesticum based on sequencing ITS rDNA region. DNA was isolated from leaves of plant and then amplified using F1 and R1 primers. Nucleotides sequences identified using Sequence Scanner Software Programm version 1.0, nucleotides sequences from ITS1, 5.8S, and ITS2 region has been mergered using EditSeq and SegMan in software Suite for Sequence Analysis DNASTAR Lasergene DM version 3.0.25. The result of this research showed that exploration data recorded there were 29 cultivars of duku, kokosan and langsat consisting of 19 dukus, 2 kokosans and 8 langsats from all horticulture centers in Indonesia. Based on macro and micromorphological caracterization and identification exhibited that taxonomi status of duku, kokosan and langsat as one genus is Lansium, and species, namely Lansium domesticum and for category of infraspecies divide into two group were duku group and kokosan-langsat groups. Phenetic relatedness among duku, kokosan and langsat from Indonesia using random amplified polymorphic DNA (RAPD) markers with eleven primers showed that yielded a total of 122 DNA bands, of which 105 were polymorphic. Primer OPB-07, OPT-16, OPU-14 and OPU-19 produced all of the polymorphic DNA bands. The size of the amplified DNA fragments ranged from 65-1200 bp. DNA was isolated from leaves of plant and then amplified using F1 and R1 primers showed that DNA fragments ranging in size from 785 bp-973 bp. Different of DNA fragments indicated polymorphism among duku, kokosan and langsat. Based on morphological and molecular approaches placed duku, kokosan and langsat in the genus of Lansium and included as a species of L. domesticum, as well defined as two groups namely L. domesticum group duku and L. domesticum group kokosan-langsat.